Pengaruh E - Tax, Pengetahuan Perpajakan Dan Tarif Pajak Terhadap Kepatuhan Pajak Orang Pribadi - Audrey Alexandra, Ngadiman (Jurnal Paradigma Akuntansi, 2021)
This study aims to examine and determine the effect of e-tax, tax knowledge and tax rates on individual taxpayer compliance. The sampling technique in this study is the Probability Sampling method with the Simple Random Sampling method. This research was conducted by distributing questionnaires online with a total of 100 samples and managed using the SmartPLS 3.2.9 program. The results of this study state that e-tax does not have a significant effect on individual taxpayer compliance. While, tax knowledge and tax rates have a significant positive effect on compliance with individual taxpayers.